أثر عوامل النجاح الحاسمة على تعزيز الأسبقيات التنافسية من خلال الذكاء الاستراتيجي -دراسة حالة مطاحن بلغيث الكبرى -سوق أهراس- - أحلام بوطوبة; مريم ملاوحية (My University, 2023)
This study aims to recognize the impact of the critical success factors on enhancing the competitive periorities, through the intermediary role of strategic intelligence at the grandsMoulinsBelghith – Souk Ahras, and to achieve the objectives of the study, the analytical descriptive approach was followed, and the questionnaire was used as the main tool of the study, to answer study questions and test their hypotheses, In order to answer the study questions and test its hypotheses, the Spss and SmartPLS4 programs were used, using structural equation modeling (SEM).And after conducting descriptive analysis of the study's data and testing its hypotheses, the study found a positive correlation between the study's variables, In addition to the indication of the size of the direct and indirect effect of the critical success factors on competitive priorities through strategic intelligence as a mediating variable, and this mediation was partial and complementary. And in the light of the results reached, the study presented a set of recommendations that would help enterprises in general and the GrandsMoulinsBelghith – Souk Ahras Company in particular to improve the levels of adoption of critical success factors and strategic intelligence reflected in the enhancement of competitive periorities. ............................................. تهدف هذه الدّراسة للتعرّف على أثر عوامل النجاح الحاسمة على تعزيز الأسبقيات التنافسية، من خلال الدور الوسيط للذكاء الاستراتيجي في شركة مطاحن بلغيث الكبرى-سوق اهراس، ولتحقيق أهداف الدراسةتم إتباع المنهج الوصفي التحليلي، وقد استخدمتالاستبانةكأداة رئيسية للدراسة، وللاجابة على أسئلة الدراسة واختبار فرضيّاتها، تمّ استخدام برنامجالSpss، والSmartPLS4 وذلكباستخدام نمذجة المعادلة الهيكلية(SEM)، وبعد إجراء عملياتالتحليل الوصفيلبيانات الدراسة واختبار فرضياتها، توصلت الدراسة لوجودعلاقة ارتباط موجبةبين متغيرات الدّراسة،بالإضافة الى دلالة حجم الاثر المباشر وغير المباشر لعوامل النجاح الحاسمة على الاسبقيات التنافسية من خلال الذكاء الاستراتيجي كمتغير وسيط،وكانت هاته الوساطة جزئية تكميلية. وفي ضوء النتائج المتوصّل إليها، قدّمت الدراسة مجموعة من التوصيات التي من شأنها أن تساعد المؤسسات بشكل عام وشركة مطاحن بلغيث الكبرى بشكل خاص على تحسين مستويات تبنّي عوامل النجاح الحاسمةوالذكاء الاستراتيجي الذي ينعكس على تعزيز الاسبقيات التنافسية. ....................................... This study aims to recognize the impact of the critical success factors on enhancing the competitive periorities, through the intermediary role of strategic intelligence at the grandsMoulinsBelghith – Souk Ahras, and to achieve the objectives of the study, the analytical descriptive approach was followed, and the questionnaire was used as the main tool of the study, to answer study questions and test their hypotheses, In order to answer the study questions and test its hypotheses, the Spss and SmartPLS4 programs were used, using structural equation modeling (SEM).And after conducting descriptive analysis of the study's data and testing its hypotheses, the study found a positive correlation between the study's variables, In addition to the indication of the size of the direct and indirect effect of the critical success factors on competitive priorities through strategic intelligence as a mediating variable, and this mediation was partial and complementary. And in the light of the results reached, the study presented a set of recommendations that would help enterprises in general and the GrandsMoulinsBelghith – Souk Ahras Company in particular to improve the levels of adoption of critical success factors and strategic intelligence reflected in the enhancement of competitive periorities.